Pandangan Teologi Rasul Paulus Tentang Keselamatan dan Implikasinya Terhadap Orang Percaya di Tinjau dari Roma 10:9 (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
From the beginning of creation, God had forbidden the fruit of the knowledge of good and evil, warning that anyone who ate it would face death. However, this warning was ignored when Eve, tempted by Satan's persuasion, chose to disobey God's command. This action led to sin, as it reflected a wrong decision and went against God's will. Originally, Adam and Eve lived in a state of holiness and freedom from sin. God Himself stated that humans were created in His image and likeness, meaning they possessed a purity and nobility that reflected His love. However, their decision to eat the forbidden fruit removed that purity. As a result, humans were separated from God's holiness and fell into sin. This is the basis for the teaching affirmed in Romans 3:23, which states that "all have sinned and fall short of the glory of God." This wrong choice had profound consequences, illustrating the importance of obedience to God's commands for maintaining purity and an intimate relationship with Him.